2019
DOI: 10.1089/soro.2018.0075
|View full text |Cite
|
Sign up to set email alerts
|

Folded-Tube Soft Pneumatic Actuators for Bending

Abstract: This paper discusses and contests the claims of "Soft Pneumatic Actuator Fascicles for High Force and Reliability" a research article which was originally published in the March 2017 issue of the Journal Soft Robotics. The original paper claims that the summed forces of multiple thin-walled extending McKibben muscles are greater than a volumetrically equivalent actuator of the same length at the same pressure. The original paper also claims that the purported benefit becomes more pronounced as the number of sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Tubes made with inextensible materials with folds have been used to realize smooth or jointed deformations using thermoplastic films (Nishioka et al, 2012(Nishioka et al, , 2017Amase et al, 2015;Sareen et al, 2017). Bending actuators using inflatable bellows and folded tubes have been developed capable of large forces and deformations (Best et al, 2015;Felt, 2019). The use of anisotropic textiles has been used to make bending actuators for wearable applications (Cappello et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Tubes made with inextensible materials with folds have been used to realize smooth or jointed deformations using thermoplastic films (Nishioka et al, 2012(Nishioka et al, , 2017Amase et al, 2015;Sareen et al, 2017). Bending actuators using inflatable bellows and folded tubes have been developed capable of large forces and deformations (Best et al, 2015;Felt, 2019). The use of anisotropic textiles has been used to make bending actuators for wearable applications (Cappello et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it was concluded that this model is best suited for actuators with relatively large aspect ratios, It may be reasonably hypothesized that model accuracy increases for actuators with increasingly similar aspect ratio to those presented by Felt in ( Felt 2019 ), the work from which the model presented here is derived. Leaving out specimen D2 and fitting a linear relation to aspect ratio and mean model error, the aspect ratio used by Felt (80/58 mm = 1.38) projects an error of nearly zero.…”
Section: Resultsmentioning
confidence: 72%
“…Based on the biomechanics data set forth by winter in ( Winter 2009 ), and assuming a nominal body mass of 62 kg ( Walpole et al, 2012 ), the nominal static torque required to hold the leg at 30° hip flexion is 19.8 Nm. In order to determine necessary dimensions for the pneumatic rotary actuators to achieve this target torque, a physical model was developed based on the model presented by Felt ( Felt 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Robotic actuators are generally developed based on the structural transformation with origami [ 90 , 143 , 163 , 164 , 165 , 166 ]. Kim et al, presented a soft fluidic bending actuator with gripping capability [ 166 ].…”
Section: Applicationsmentioning
confidence: 99%